The relationship between stock market volatility and equity returns : evidence from Malaysia / Azlina Celestinus - Celestinus, Azlina (2016)
The equity return are vary every time and researchers keep on predicting the return by using different stock market variables and even by using macroeconomics variables, which the equity return also contributed to the economic growth especially in Malaysia. However, it is believed that the equity returns are hardy predictable because of the stock market volatility. Thus, in this study, instead of using the specific firm's variables or macroeconomics variables, we want to know whether there is any negative or positive relationship between stock market volatility and equity returns.